Zmena kognitívnych funkcií počas akútnej zmätenosti po brušných operáciach - Vörösová, Gabriela; Pilárik, Ľubor; Šabíková, Mária (Ošetrovateľstvo, 2012)
Introduction: Cognitive impairment after abdominal surgeries is the most frequently manifested as postoperative delirium/acute confusion. The assessment of patient´s cognitive status is an important part of care management. Objective: The objective of the study was to show the changes in cognitive functions through the SMMSE (The Standardized Mini-Mental State Examination) in patients after abdominal surgeries that were diagnosed with acute confusion. Methodology and Sample: We used the translated Slovak version of the SMMSE presented by Vajdičková & Kolibáš (2000). The scale was applied in n = 111 purposively selected participants, the 65-85 year-old patients with acute confusion who were assessed minimally 3 times (on the 1st, 4th and 7th days of acute confusion). We used Fischerov F test (ANOVA) and Student´t-test for statistical data processing. Results: The statistically significant differences in cognitive functions were not found between the genders. The differences were found in the groups according to age on the 4th day between the 1st group (65-75 year-olds), the 2nd group (76-80 year-olds) vs. the 3rd group (81-85 year-olds). There were significant differences between individual measurements and diagnoses in the comparison according to the diagnoses (K35, K80, K56, K40, K25, and C18). Conclusion: The expected differences in cognitive functions were found in the groups according to age and diagnoses of abdominal surgeries. Fluctuating cognition is one of the defining characteristics of nursing diagnosis Acute Confusion.
Keywords: Statistics as Topic; Female; Acute Disease; Nursing Diagnosis; delirium; statistika jako téma; Age Factors; kognitivní poruchy; ženské pohlaví; Nursing Research; břicho; Surgery Department, Hospital; chirurgie operační; zmatenost; věkové faktory; lidé; Inpatients; Delirium; Mental Status Schedule; pooperační komplikace; Aged, 80 and over; Abdomen; Cognition Disorders; prospektivní studie; Confusion; Male; Postoperative Complications; Aged; Prospective Studies; Standardized Mini-Mental State Examination (SMMSE); ošetřovatelský výzkum; záznam o duševním stavu; akutní nemoc; ošetřovatelská diagnóza; senioři nad 80 let; senioři; mužské pohlaví; chirurgické oddělení nemocnice; Surgical Procedures, Operative; hospitalizovaní pacienti; Humans